Anti-Müllerian hormone and letrozole levels in boys with constitutional delay of growth and puberty treated with letrozole or testosterone - E Kohva; T Varimo; H Huopio; S Tenhola; R Voutilainen; J Toppari; P J Miettinen; K Vaaralahti; J Viinamaki; J T Backman; M Hero; T Raivio (OXFORD UNIV PRESS, 2025)
STUDY QUESTION: Does treatment of constitutional delay of growth and puberty (CDGP) in boys with aromatase inhibitor letrozole (Lz) or conventional low-dose testosterone (T) have differing effects on developing seminiferous epithelium?
SUMMARY ANSWER: Anti-Mullerian hormone (AMH) declined similarly in both treatment groups, and the two Sertoli cell-derived markers (AMH and inhibin B (iB)) exhibited differing responses to changes in gonadotrophin milieu.
WHAT IS KNOWN ALREADY: Boys with CDGP may benefit from puberty-inducing medication. Peroral Lz activates gonadotrophin secretion, whereas intramuscular low-dose T may transiently suppress gonadotrophins and iB.
STUDY DESIGN, SIZE, DURATION: Sera of 28 boys with CDGP who participated in a randomised, controlled, open-label trial at four paediatric centres in Finland between August 2013 and January 2017 were analysed. The patients were randomly assigned to receive either Lz (2.5 mg/day) (n = 15) or T (I mg/kg/month) (n = 13) for 6 months.
PARTICIPANTS/MATERIALS, SETTING, METHODS: The 28 patients were at least 14 years of age, showed first signs of puberty, wanted medical attention for CDGP and were evaluated at 0, 3, 6 and 12 months of visits. AMH levels were measured with an electrochemiluminescence immunoassay and L2 levels with liquid chromatography coupled with tandem mass spectrometry.
MAIN RESULTS AND THE ROLE OF CHANCE: AMH levels decreased in both treatment groups during the 12-month follow-up (P < 0.0001). Between 0 and 3 months, the changes in gonadotrophin levels (increase in the Lz group, decrease in the T group) correlated strongly with the changes in levels of iB (FSH vs iB, r = 0.55, P=0.002; LH vs iB, r =0.72, P <0.0001), but not with the changes in AMH (P = NS). At 12 months, AMH levels did not differ between the groups (P = NS). Serum Lz levels (range, 124-1262 nmol/L) were largely explained by the Li dose per weight (at 3 months r= 0.62, P= 0.01; at 6 months r =0.52, P= 0.05). Lz levels did not associate with changes in indices of hypothalamic-pituitary-gonadal axis activity or Sertoli cell markers (in all, P = NS).
LIMITATIONS, REASONS FOR CAUTION: The original trial was not blinded for practical reasons and included a limited number of participants.
WIDER IMPLICATIONS OF THE FINDINGS: In early puberty, treatment-induced gonadotrophin stimulus was unable to counteract the androgen-mediated decrease in AMH, while changes in iB levels were associated with changes in gonadotrophin levels. AMH decreased similarly in both groups during the treatment, reassuring safety of developing seminiferous epithelium in both treatment approaches. Since a fixed dose of Li induced variable serum Lz levels with a desired puberty-promoting effect in all boys, more research is needed to aim at a minimal efficient dose per weight.